Charakterystyka ekofizjograficzna rejonu Nowogrodu Bobrzańskiego = Eco-physiographic characteristics of the Nowogród Bobrzański area - Asani, Anna; Gawron, Marta; Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the eco-physiographic characteristics of the Nowogród Bobrzański area. There are analyzed in detail the various components of the environment and the state of preservation of landscape and opportunities for their development. Selection of research area has been conditioned by the operation of natural aggregate from the Bóbr river bed, which takes place in Nowgoród Bobrzański and attempt to assess the impact of these projects on the environment.
Keywords: ekofizjografia; Bóbr (rzeka); eksploatacja kruszywa naturalngo; eco-physiography; Bóbr River; exploitation of natural aggregate